2010
DOI: 10.1103/physreva.81.043425
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies of x-ray scattering from three-dimensionally-aligned asymmetric-top molecules

Abstract: We theoretically and numerically analyze x-ray scattering from asymmetric-top molecules three-dimensionally aligned using elliptically polarized laser light. A rigid-rotor model is assumed. The principal axes of the polarizability tensor are assumed to coincide with the principal axes of the moment of inertia tensor. Several symmetries in the Hamiltonian are identified and exploited to enhance the efficiency of solving the time-dependent Schrödinger equation for each rotational state initially populated in a t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 115 publications
(185 reference statements)
1
38
0
Order By: Relevance
“…It is known from the literature [4,23] and confirmed by our calculation that it is the product F ≡ I * τ , i.e., the fluence of the aligning laser pulse, that ρ(φ, θ, χ, t) depends on. This reduces the number of parameters from three to two, namely, {F, T rot }.…”
Section: Uncertainties In the Alignment Distribution Function And supporting
confidence: 63%
See 2 more Smart Citations
“…It is known from the literature [4,23] and confirmed by our calculation that it is the product F ≡ I * τ , i.e., the fluence of the aligning laser pulse, that ρ(φ, θ, χ, t) depends on. This reduces the number of parameters from three to two, namely, {F, T rot }.…”
Section: Uncertainties In the Alignment Distribution Function And supporting
confidence: 63%
“…Field-free molecular alignment Theories of molecular alignment by an external laser pulse have been given in the literature [4][5][6]23] and there is no need to repeat them here. These theories are based on the rigid rotor approximation and tell how the molecular rotational wavepacket evolves with time in the presence of an external laser field.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of GED is that the random orientation of the molecules in the gas phase greatly reduces the information content of the diffraction patterns. It has been shown that a diffraction pattern from perfectly aligned molecules contains sufficient information to retrieve the structure directly from the diffraction pattern, without the need for comparison with a theoretical model [13,14]. It is, however, so far not possible to experimentally produce perfectly aligned molecules in the gas phase for diffraction experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Clean molecular samples can be generated by their spatial separation according to shape [13][14][15] and size [16]. Controlling the spatial orientation of the molecules leads to an enhancement of the information that can be retrieved from a diffraction pattern, as proposed theoretically [17][18][19][20] and demonstrated experimentally for x-ray [21,22] as well as for electron diffraction [23,24]. Strong alignment or orientation is generally necessary [11,20] for three-dimensional structure reconstruction [24] and can be provided in cold supersonic molecular beams by strong-field laser alignment and mixed-field orientation [25][26][27][28][29].…”
mentioning
confidence: 99%